EFEKTIVITAS PELAKSANAAN PROGRAM PELATIHAN PENGEMBANGAN DESAIN KEMASAN PRODUK BATIK SEMANGGI SURABAYA - Susi Hardjati; Muchlisiniyati Safeyah; Kalvin Edo Wahyudi (Journal Publicuho, 2021)
Semanggi batik is a typical batik of Surabaya City which has problems in increasing competitiveness, especially in the aspect of packaging quality. Therefore, a Semanggi batik product packaging design training program was implemented. The purpose of this training is to increase the understanding and skills of the semanggi batik craftsmens in developing product packaging designs. This article aims to measure and describe the effectiveness of the implementation of the packaging design development program for semanggi batik Surabaya products. The research was conducted with a quantitative approach with data collection techniques using a questionnaire. The data analysis technique used descriptive analysis. The results showed that the effectiveness of the implementation of the training program for the packaging design development of semanggi batik Surabaya products can be categorized as very high. This is because all aspects to measure the effectiveness of program implementation, such as compliance with implementation procedures, the degree of delivery of benefits to targets, the degree of change felt by target groups and differences between program outcomes and objectives have been optimally fulfilled.